2015
DOI: 10.1016/j.neuron.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fluctuations and Non-linear Ignitions: Two Dynamic Faces of Cortical Recurrent Loops

Abstract: Recent human neurophysiological recordings have uncovered two fundamental modes of cerebral cortex activity with distinct dynamics: an active mode characterized by a rapid and sustained activity ("ignition") and a spontaneous (resting-state) mode, manifesting ultra-slow fluctuations of low amplitude. We propose that both dynamics reflect two faces of the same recurrent loop mechanism: an integration device that accumulates ongoing stochastic activity and, either spontaneously or in a task-driven manner, crosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 119 publications
10
92
0
Order By: Relevance
“…These results are important because they extend the previously reported findings of failure to become aware of specific V1 activation patterns (16), to high-order visual areas, whose activity has been consistently demonstrated to be more closely linked to perceptual awareness (45,46). Together, these findings argue against the suggestion that the slow spontaneous fluctuations reflect stream of conscious thoughts and images, but rather that this activity remains largely subliminal (47)(48)(49).…”
Section: Increased Activation In High-order Areas Does Not Necessarilysupporting
confidence: 78%
“…These results are important because they extend the previously reported findings of failure to become aware of specific V1 activation patterns (16), to high-order visual areas, whose activity has been consistently demonstrated to be more closely linked to perceptual awareness (45,46). Together, these findings argue against the suggestion that the slow spontaneous fluctuations reflect stream of conscious thoughts and images, but rather that this activity remains largely subliminal (47)(48)(49).…”
Section: Increased Activation In High-order Areas Does Not Necessarilysupporting
confidence: 78%
“…The recognition of the "default mode" network (26) started a long-lasting interest in the significance of the human brain's ongoing or intrinsic activity, which is characterized by synchronous USFs of activity, often taking seconds to develop (18). USFs have been recorded in the cortex of awake humans and primates, and also under anesthesia (27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…Recordings in humans indicate that ongoing activity constantly fluctuates in a tightly correlated manner across distant brain regions, forming reproducible patterns with rich temporal dynamics and spatial organization (18). The potential contribution of spontaneous activity to conscious processing has been suggested and simulations helped characterize two main modes of activity: an active mode characterized by rapid and sustained activity ("ignition") (19), which contributes to the signature of "conscious access," and a resting mode with spontaneous ultraslow (<0.1 Hz) fluctuations (USFs) (18). It has been suggested that ignition and ultraslow spontaneous fluctuations share similar mechanisms (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If this feed-forward spread or 'ignition' does not happen, conscious perception does not occur [45]. If it does happen, a great deal of arguably unconscious processing takes place in the global workspace, before ...…”
Section: 32mentioning
confidence: 99%